Biological based ecotourism potential in the complex of protected areas Oti-Keran-Mandouri (Togo, West Africa). Issue 1 (2nd January 2022) - Koumantiga, Dabitora; Wala, Kpérkouma; Diwediga, Badabaté; Kanda, Madjouma; Dourma, Marra; Batawila, Komlan; Akpagana, Koffi
ABSTRACT: In Togo, the Oti-Kéran-Mandouri (OKM) complex had important biological-oriented tourism activities in 1980s. However, degradation of ecosystems has negatively affected the biological resources of these protected areas. This study aims at analysing the current biological-based ecotourism potential of the OKM complex facing conservation challenges. To this end, a mixed approach combining fauna and flora inventories with ethnobotanical surveys was adopted.. Results showed that the floristic potential is characterized by 287 species distributed into 63 botanical families and 170 genera. A total of 26 and 19 woody species were identified as species with 'high cultural value' and 'high attractive potential', respectively. In terms of animal diversity, 11 species of the large wildlife, including emblematic species, have been recorded. Six of these animal and plant species are reported in the IUCN Red List. These findings provide insights on the great potential of OKM complex for ecotourism promotion in Togo.